Hemodialysis Catheter-Related Infection in a Teaching Hospital of Central Nepal - Sedhain, Arun; Sapkota, Abja; Mahotra, Narayan B (Journal of Institute of Medicine Nepal, 2019)
Introduction: Infection of the central venous catheter (CVC) is a major complication seen among patients undergoing hemodialysis. Identifying CVC related infection (CRI) and its risk factors and causative organisms is important for better implementation of preventive strategies. Methods: A prospective study was conducted at Chitwan Medical College for duration of 2 years from January 2017to December 2018 among the patients undergoing hemodialysis via CVC. The data collected were related to patients’ demographics, site of catheter insertion, and duration, microbiological data including cultures from catheter sites, blood, and catheters’ tips and antibiotic sensitivity. Catheter related infection was divided into catheter related local infection (CRLI) and catheter related blood stream infection (CRBSI). Data was analyzed using IBM SPSS Statistics version 21.0. Results: A total of 41 cases of CVC related infection (CRI) were documented with an incidence rate of 6.94 episodes per 1000 catheter days at risk. Out of the total CRI, 39.02% were CRLI and 60.98% were CRBSI. Fever with chills and rigor were the most common clinical presentation. Risk factors for the development of CRI were duration of catheter in situ, repeated change of CVC and the use of CVC for indications other than hemodialysis (HD).Staphylococci and Klebsiella were the most common organisms isolated in culture. Conclusion: The rate of CRI among Nepalese patients undergoing hemodialysis is high. Prolonged duration of CVC usage, recent change of catheter and the use of the HD catheter for the purpose of institution of intravenous medication have been found as the risk factors for CRI.